Refugee cities : how Afghans changed urban Pakistan - Alimia, Sanaa (University of Pennsylvania Press, 2022)
Situated between the 1970s Soviet Union's invasion of Afghanistan and the post-2001 War on Terror, Refugee Cities tells the story of how global wars affect everyday life for Afghans who have been living as refugees in Pakistan. This book provides a necessary glimpse of what ordinary life looks like for a long-term refugee population, beyond the headlines of war, terror, or helpless suffering. It also increases our understanding of how cities--rather than the nation--are important sites of identity-making for people of migrant origins.In Refugee Cities, Sanaa Alimia reconstructs local microhistories to chronicle the lives of ordinary people living in low-income neighborhoods in Peshawar and Karachi and the ways in which they have transformed the cities of which they are a part. In Pakistan, formal citizenship is almost impossible for Afghans to access; despite this, Afghans have made new neighborhoods, expanded city boundaries, built cities through their labor in construction projects, and created new urban identities--and often they have done so alongside Pakistanis. Their struggles are a crucial, neglected dimension of Pakistan's urban history. Yet given that the Afghan experience in Pakistan is profoundly shaped by geopolitics, the book also documents how, in the War-on-Terror era, many Afghans have been forced to leave Pakistan. This book, then, is also a documentation of the multiple displacements migrants are subject to and the increased normalization of deportation as a part of "refugee management."